Synergistic effects of diet and exercise on hippocampal function in chronically stressed mice. (12th November 2015) - Hutton, C.P.; Déry, N.; Rosa, E.; Lemon, J.A.; Rollo, C.D.; Boreham, D.R.; Fahnestock, M.; deCatanzaro, D.; Wojtowicz, J.M.; Becker, S.
Highlights: Chronic unpredictable stress induces anhedonia and hypertrophy of adrenal glands. Exercise, but not diet, upregulates neurogenesis in the absence of chronic stress. Chronic stress abolishes the enhancement of neurogenesis by exercise. Diet with exercise raises hippocampal BDNF, neurogenesis and size in stressed mice. Diet and exercise interact to alleviate anhedonic behavior. Abstract: Severe chronic stress can have a profoundly negative impact on the brain, affecting plasticity, neurogenesis, memory and mood. On the other hand, there are factors that upregulate neurogenesis, which include dietary antioxidants and physical activity. These factors are associated with biochemical processes that are also altered in age-related cognitive decline and dementia, such as neurotrophin expression, oxidative stress and inflammation. We exposed mice to an unpredictable series of stressors or left them undisturbed (controls). Subsets of stressed and control mice were concurrently given (1) no additional treatment, (2) a complex dietary supplement (CDS) designed to ameliorate inflammation, oxidative stress, mitochondrial dysfunction, insulin resistance and membrane integrity, (3) a running wheel in each of their home cages that permitted them to exercise, or (4) both the CDS and the running wheel for exercise. Four weeks of unpredictable stress reduced the animals' preference for saccharin, increased their adrenal weights and abolished the exercise-induced upregulation of neurogenesis that was observed in non-stressed animals. Unexpectedly, stress did not reduce hippocampal size, brain-derived neurotrophic factor (BDNF), or neurogenesis. The combination of dietary supplementation and exercise had multiple beneficial effects, as reflected in the number of doublecortin (DCX)-positive immature neurons in the dentate gyrus (DG), the sectional area of the DG and hippocampal CA1, as well as increased hippocampal BDNF messenger ribonucleic acid (mRNA) and serum vascular endothelial growth factor (VEGF) levels. In contrast, these benefits were not observed in chronically stressed animals exposed to either dietary supplementation or exercise alone. These findings could have important clinical implications for those suffering from chronic stress-related disorders such as major depression.